Otoritas Politik dan Elite Sosial dalam Al-Qur’an: Analisis Semantik Toshihiko Izutsu terhadap Ūlī al-Amr dan al-Malā’ - Fitra Dana Hasibuan; Muhammad Ali Azmi Nasution; Nur Fadhilah Syam (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2026)
The construction of political authority and the configuration of social elites in the Qur’an require a reading that goes beyond a normative approach that is often merely descriptive, as such a framework often ignores the dynamics of meaning that form within the network of Qur’anic concepts. This study aims to uncover the meaning structure of Ūlī al-Amr and al-Malā’ and the conceptual relationship between them through Toshihiko Izutsu’s semantic approach. The method used is qualitative, based on a literature study, with an analysis of the basic meaning as the lexical meaning attached to the word, as well as the relational meaning formed in the field of meaning through its relationship with other concepts in the Qur’an. The results of the study show that Ūlī al-Amr has a relational character as a normative authority that gains legitimacy through its attachment to the values ​​of revelation, obedience, and moral responsibility in maintaining social order. On the other hand, al-Malā’ represents a social elite that operates within a framework of power based on status, wealth, and collective influence, with a tendency to build dominance and resistance to the messages of the prophets. The conceptual relationship between the two demonstrates a dichotomy between authority grounded in normative legitimacy and power rooted in social hegemony. The theoretical implications of this study emphasize the Qur’an’s conceptual distinction between legitimate, ethically oriented authority and power structures that tend to uphold the interests of dominant groups.